Development of Asian parasitoids in larvae Of Drosophila Suzukii feeding on blueberry and artificial diet. (4th February 2018) - Girod, P.; Rossignaud, L.; Haye, T.; Turlings, T. C. J.; Kenis, M.
Abstract: In just a few years, the Asian fly Drosophila suzukii has invaded several continents and has become a very serious pest of many fruit crops worldwide. Current control methods rely on chemical insecticides or expensive and labour‐intensive cultural practices. Classical biological control through the introduction of Asian parasitoids that have co‐evolved with the pest may provide a sustainable solution on condition that they are sufficiently specific to avoid non‐target effects on local biodiversity. Here, we present the first study on the development of three larval parasitoids from China and Japan, the Braconidae Asobara japonica and the Figitidae Leptopilina japonica and Ganaspis sp., on D. suzukii . The Asian parasitoids were compared with Leptopilina heterotoma, a common parasitoid of several Drosophilidae worldwide. The three Asian species were successfully reared on D. suzukii larvae in both, blueberry and artificial diet, in contrast to L. heterotoma whose eggs and larvae were encapsulated by the host larvae. All parasitoids were able to oviposit one day after emergence. Asobara japonica laid as many eggs in larvae feeding in blueberry as in artificial diet, whereas L. heterotoma oviposited more in larvae on the artificial diet and the Asian Figitidae oviposited more in larvae feeding on blueberry. Ganaspis sp. laid very few eggs in larvae in the artificial diet, suggesting that it may be specialized in Drosophila species living in fresh fruits. These data will be used for the development of a host range testing to assess the suitability of Asian parasitoids as biological control agents in invaded regions.